Arsenic‐Mediated Activation of the Nrf2‐Keap1 Antioxidant Pathway. Issue 2 (27th November 2012) - Lau, Alexandria; Whitman, Samantha A.; Jaramillo, Melba C.; Zhang, Donna D.; Slitt, Angela L.; Hodgson, Ernest
ABSTRACT Arsenic is present in the environment and has become a worldwide health concern due to its toxicity and carcinogenicity. However, the specific mechanism(s) by which arsenic elicits its toxic effects has yet to be fully elucidated. The transcription factor nuclear factor (erythroid‐derived 2)‐like 2 (Nrf2) has been recognized as the master regulator of a cellular defense mechanism against toxic insults. This review highlights studies demonstrating that arsenic activates the Nrf2‐Keap1 antioxidant pathway by a distinct mechanism from that of natural compounds such as sulforaphane (SF) found in broccoli sprouts or tert‐butylhyrdoquinone (tBHQ), a natural antioxidant commonly used as a food preservative. Evidence also suggests that arsenic prolongs Nrf2 activation and may mimic constitutive activation of Nrf2, which has been found in several human cancers due to disruption of the Nrf2‐Keap1 axis. The current literature strongly suggests that activation of Nrf2 by arsenic potentially contributes to, rather than protects against, arsenic toxicity and carcinogenicity. The mechanism(s) by which known Nrf2 activators, such as the natural chemopreventive compounds SF and lipoic acid, protect against the deleterious effects caused by arsenic will also be discussed. These findings will provide insight to further understand how arsenic promotes a prolonged Nrf2 response, which will lead to the identification of novel molecular markers and development of rational therapies for the prevention or intervention of arsenic‐induced diseases. The National Institute of Environmental Health Science (NIEHS) Outstanding New Environmental Scientist (ONES) award has provided the opportunity to review the progress both in the fields of arsenic toxicology and Nrf2 biology. Much of the funding has led to (1) the novel discovery that arsenic activates the Nrf2 pathway by a mechanism different to that of other Nrf2 activators, such as sulforaphane and tert‐butylhydroquinone, (2) activation of Nrf2 by chemopreventive compounds protects against arsenic toxicity and carcinogenicity both in vitro and in vivo, (3) constitutive activation of Nrf2 by disrupting Keap1‐mediated negative regulation contributes to cancer and chemoresistance, (4) p62‐mediated sequestration of Keap1 activates the Nrf2 pathway, and (5) arsenic‐mediated Nrf2 activation may be through a p62‐dependent mechanism. All of these findings have been published and are discussed in this review. This award has laid the foundation for my laboratory to further investigate the molecular mechanism(s) that regulate the Nrf2 pathway and how it may play an integral role in arsenic toxicity. Moreover, understanding the biology behind arsenic toxicity and carcinogenicity will help in the discovery of potential strategies to prevent or control arsenic‐mediated adverse effects. © 2012 Wiley Periodicals, Inc. J BiochemMol Toxicol 27:99‐105, 2013; View this article online at wileyonlinelibrary.com. DOI 10.1002/jbt.21463